Exploration of copper-cysteamine nanoparticles as an efficient heterogeneous Fenton-like catalyst for wastewater treatment. (January 2022) - Pandey, N.K.; Li, H.B.; Chudal, L.; Bui, B.; Amador, E.; Zhang, M.B.; Yu, H.M.; Chen, M.L.; Luo, X.; Chen, W.
Abstract: Copper-cysteamine (Cu-Cy) is a new nanoparticle that can be stimulated by UV light, microwaves, X-rays, and ultrasound to produce various types of reactive oxygen species (ROS) for cancer and infectious disease treatments. Most importantly, our recent studies revealed that Cu-Cy nanoparticles (NPs) can be used for wastewater treatment as an effective heterogeneous Fenton-like catalyst, thereby adding one more important practical application of this interesting material. Herein, for the first time, we describe the use of Cu-Cy NPs with the assistance of hydrogen peroxide (H2 O2 ) as an oxidizing agent for the oxidative degradation of organic contaminants, particularly rhodamine B (RhB), methylene blue (MB), and 4-nitrophenol (4-NP), for wastewater treatment. Additionally, we compared two H2 O2 oxidation methods for the treatment of RhB and 4-NP: oxidation using H2 O2 /Cu-Cy with or without microwave (MW) irradiation. Our findings show that the degradation rate enhanced when activated by MW irradiation. Furthermore, recycling experiments revealed that Cu-Cy has good stability and recyclability. Overall, it is believed that the Cu-Cy/H2 O2 system studied in this work could be used in advanced oxidation processes toward the degradation of organic pollutants. Graphical abstract: Image 1 Highlights: Cu-Cy can be used as an efficient catalyst for wastewater purification. Degradation efficiency can be enhanced when excited by microwaves. OH is the dominant species responsible for the degradation of contaminants. Cu-Cy has good stability and recyclability for wastewater treatment. This work opens a new application of this fascinating material.